Multi-step Flow Synthesis of the Anthelmintic Drug Praziquantel - Phull, Manjinder Singh; Jadav, Surender Singh; Bohara, Chander Singh; Gundla, Rambabu; Mainkar, Prathama S (SynOpen, 2023)
Praziquantel (PZQ; Brand name: Biltricide) is categorized as an anthelminthic drug, and it is used for the treatment of Schistosomiasis and other parasitic infections. The World Health Organization (WHO) has classified it as one of the essential and emergency medicines needed across the globe. The price of PZQ formulated product depends on the associated method of preparation, along with cost of raw materials. A precise and reliable method for the preparation of PZQ using a flow-chemistry approach is described in this study using phenylethylamine as the starting material. The main objective of the present study is to identify a new economical route for the synthesis of PZQ that could decrease the production time drastically from days to minutes and be transferred to large-scale production. Simultaneously, the purity of the obtained intermediates in essential steps, as single or continuous process, determined by HPLC analysis were more than 90% pure. The continuous preparation process of PZQ in the current study was achieved in less time (ca. 3–4 h) than using conventional methods (ca. 3–4 days). Moreover, the required quantity of key intermediate dimethoxyethanamine is 40–50% less than in existing methods.
Keywords: Praziquantel; flow chemistry; optimization; continuous process; essential medicine